Study on surface roughness quality of FDM and MJM additive manufacturing model for implementation as investment casting sacrificial pattern / MN Hafsa ... [et al.] - Hafsa, MN; Kassim, N; Ismail, S; Kamaruddin, SA; Hafeez, TM (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Additive Manufacturing (AM) technology is relatively new and has developed with diverse research activity to implement AM in every possible manufacturing process. Its implementation in the Investment Casting (IC) is one of development in AM technology. Traditionally, the wax IC pattern was prepared using an injection molding process. Compared to the traditional method, AM could shorten the process by a considerable margin. This study is made to identify the capability of Multi-Jet Modeling (MJM) and Fused Deposition Modeling (FDM) techniques to produce an IC pattern within the desired surface quality. The AM part is fabricated with varying process, internal structure pattern, and part build orientation, and the fabricate part is tested using a surface roughness tester to get the average surface roughness value. The results show that part built with 90º built orientation produced a better result compared to part built with 0º built orientation. Also, parts with hatch internal support structure would produce better surface quality compared to the others. Generally, AM techniques are capable to produce a good surface quality for sacrificial IC pattern.